On equitable coloring of corona of wheels - J. Vernold Vivin; K. Kaliraj (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2016)
The notion of equitable colorability was introduced by Meyer in 1973 meyer. In this paper we obtain interesting results regarding the equitable chromatic number χ_= for the corona graph of a simple graph with a wheel graph G° W_n. Some extensions into l-corona products are also determined.